Comparing cash and food transfers: Findings from a pilot project in Sri Lanka - Mohiddin, Lili; Sharma, Manohar; Haller, Anette (Emergency Nutrition Network, 2007)
The key objective of the study described here was to compare the impact of cash and food transfers on beneficiary households’ food and livelihood security and on the local economy. A wider objective was to learn how best to determine the feasibility and appropriateness of cash-based programmes in emergency food-security assessments... In areas where markets were functioning and accessible, cash transfer was more cost-effective and preferred by beneficiaries. In those areas where markets were less functional or accessible food assistance was more cost-effective and preferred by beneficiaries. The appropriateness of cash programming depends on market access and functioning. (whether they are competitive and integrated), and security. Food aid is more appropriate in contexts where markets are not working well, where security conditions impose higher market transactions costs for consumers, and in situations of high and unpredictable inflation. Opportunities exist for using both interventions in parallel or in a phased approach depending on seasonal and contextual changes over time and space.